Effects of dietary chitosan oligosaccharides on oxidative stress and inflammation response in liver and spleen of yellow-feather broilers exposed to high ambient temperature. Issue 1 (18th November 2020) - Lan, Ruixia; Wei, Linlin; Chang, Qingqing; Wu, Shengnan; Zhihui, Zhao
Abstract: Heat stress jeopardised animal health by inducing oxidative stress and inflammation. This study was done to investigate the effects of chitosan oligosaccharides (COS) on oxidative stress and inflammation response in liver and spleen of yellow-feather broilers under high ambient temperature. A total of 144 35-day-old female Chinese indigenous yellow-feather broilers (body weight 450.21 ± 10.05 g) were randomly allocated into 3 dietary treatments with 6 replication pens, each pen had 8 broilers. The treatments were: Control, basal diet; COS100, basal diet with 100 mg/kg COS; COS200, basal diet with 200 mg/kg COS. During day 22 to 42 (57 to 77 days of age), broilers in the COS200 group had higher ( p <  .05) ADFI than broilers in the Control group. Broilers in the COS200 group had lower ( p <  .05) serum alanine aminotransferase, aspartate aminotransferase, and tumour necrosis factor-α levels, and spleen malondialdehyde (MDA) content, but had higher ( p <  .05) liver superoxide dismutase activity and serum interleukin-10 level than broilers in the Control group. Broilers in the COS100 and COS200 groups had lower ( p <  .05) serum and liver MDA content, and serum interleukin-1β level, but had higher ( p <  .05) serum glutathione peroxidase activity than broilers in the Control group. In conclusion, dietary COS supplementation can alleviate heat stress-induced oxidative stress and inflammation response in liver and spleen by decreasing lipid peroxidation, increasing anti-oxidant enzyme activities and IL-10 level. HIGHLIGHTS: Dietary COS decreased serum ALT, AST, IL-1β, TNF-α and MDA. Dietary COS increased serum GSH-Px and IL-10, liver SOD, and spleen GSH-Px.